Navigating Economic Landscapes: Strategic Insights Amidst the Pandemic and Beyond - Ibrahim, Azharsyah (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
The issue summarizes a series of research studies related to Islamic economics and finance. The first study focuses on the impact of the COVID-19 pandemic on economic growth in Muslim and non-Muslim countries, highlighting the differing effects of mobility restrictions and other pandemic-related factors. Other studies examine topics such as factors influencing foreign direct investment in Muslim countries, zakat compliance among Indonesian business owners, the integration of Bitcoin within the Indonesian monetary system, and the impact of fintech on charitable giving practices among millennials in Java. Additionally, research on Islamic banking performance, management accounting information system quality in Islamic banks, and strategic recommendations for the economic sustainability of business units within Dayah in Aceh are discussed. This issue also covers studies on halal service performance, challenges faced by halal-certified MSMEs, impulsive buying behaviors among Generation Z in Aceh, a Falah-based welfare index, cultural values as an anti-fraud strategy in Islamic schools, and the optimization of Hajj finance in Indonesia through the role of Wakalah contracts. The studies employ rigorous methodologies to achieve their objectives and their findings offer valuable insights with significant implications for the field of Islamic economics and finance, including areas like Islamic banking performance, halal service performance, and the optimization of Hajj finance.